Keanekaragaman Jenis Liana Berkayu di Hutan Dataran Rendah Taman Nasional Lore Lindu Sulawesi Tengah Indonesia - Wahyu Mohammad; Ramadhanil Ramadhanil; Samsurizal M. Suleman (Biocelebes, 2014)
Research entitled "The Woody Liana Diversity in the Lowland forest of The Lore Lindu National Park (LLNP) Central Sulawesi Indonesia has been conducted from April to June 2014. The objectives of research was to obtain the data of liana diversity in the lowland forest of LLNP around the Bobo village, Palolo District The study used a survey method in which samples are taken using the method of double swath plot size 5 X 5 amount 14 subplots arranged in purposive sampling. All recognizable morphospecies of liana plants were collected. Plant collecting was according to the “Schweinfurth method” (Bridson and Forman 1999). Additionally, fertile voucher specimens were collected for identification purposes. Processing of the specimens was conducted at the Herbarium Celebense (CEB), Universitas of Tadulako, Palu. Identification was done in the field, in CEB, and at the Laboratory of Biodiversity Department of Biology Faculty of Basic Sciences Tadulako University Vouchers were deposited in CEB, and at the Laboratory of Biodiversity Faculty of Basic Sciences Tadulako University Palu. The results showed that there were 35 (Thirtyfive) woody liana species in the studied area. Dinochloa scanden was the highest Important Value (19,91%), whereas the liana species with the lowest of Value index was Capparis quinifolia (INP 1,49%). We noted that there were a number liana species were Endemic to Sulawesi and Wallacea region namely: Calamus minahassae, Calamus zollingerii, Korthalsia celebica, Strongilodon celebicus and Artrabotrys trichofolius. Based on the Shanon-Whiener Index that the liana diversity of lowland rain forest of Bobo Village was chategorized very high with the H’ 3,27. Keywords: Lore Lindu National Park, the village of Bobo, Diversity, Liana